A variant of the method of characteristics - Šayar, Mario; Virag, Zdravko; Korbar, Radoslav (Computer Assisted Methods in Engineering and Science; Vol 9 No 4 (2002), 2023)
A variant of the method of characteristics for hyperbolic conservation laws is proposed in this paper. It is based on the time interpolation instead of space interpolation as in the standard method of characteristics. A new method for calculating the propagation velocity is proposed as well. The numerical results of some presented typical tests indicate that algorithm is very accurate.